(3QSGdI eYQaI HGdeQJHI GdTghOjI aj efRdI GdhLhOjIs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Rjf LjO hLhOfG HfhQ GdEjeGf CeG HYO Cf Gddg SHMGfg HebJVi CSeGA PGJg GddGReg dceGdg ef jahJ LeGdg hUaGJ LdGdg LYd GdCTjGA eJaGhJg ai eQGJH CMhGdgG s
(3BNQgG (B:s
(3hbO ChVMJ gPg GdbVjI ai QSGdJi GdeSeGI HGdeQJHI GdTghOjI ai GdefRdI GdhLhOjI hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B18s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs